Data access optimizations for highly threaded multi-core CPUs with multiple memory controllers - Hager, Georg; Zeiser, Thomas; Wellein, Gerhard (Proceedings of the 2008 IEEE International Parallel & Distributed Processing Symposium, 2008)
Processor and system architectures that feature multiple memory controllers are prone to show bottlenecks and erratic performance numbers on codes with regular access patterns. Although such effects are well known in the form of cache thrashing and aliasing conflicts, they become more severe when memory access is involved. Using the new Sun UltraSPARC T2 processor as a prototypical multi-core design, we analyze performance patterns in low-level and application benchmarks and show ways to circumvent bottlenecks by careful data layout and padding. ©2008 IEEE.
UnivIS-Import:2015-04-16:Pub.2008.zwiss.rrze.zensys.dataac_6